Dioxin Control in the Co-processing of Waste Printed Circuit Board and Copper Concentrate with an Ausmelt Furnace - Wei Li; Jia Sun; Deng-Feng Ma; Xian-Long Liu; Sheng Li; Jian-Ye Bei; Ming-Xiu Zhan; Xiao-Qing Lin; Tong Chen (Aerosol and Air Quality Research)
Abstract In recent years, with the rapid growth of the amount of electronic equipment, the environmental pollution caused by waste printed circuit board (WPCB) has become increasingly serious. Co-processing of WPCB and copper concentrate is an economic and effective way to realize the resource utilization of WPCB. However, there are few reports on the inhibition of dioxin by high concentration of SO2 generated from copper concentrate during co-processing. From the perspective of dioxin distribution, the effects of different co-processing ratios, SO2 concentration and other factors were systematically studied. The actual environment of the Ausmelt furnace was simulated by using a laboratory tubular furnace, and the emission characteristics of dioxins were investigated. Compared with the disposal of WPCB alone, the total concentration and toxic equivalent quantity (TEQ) of dioxins decreased by 14.7–26.8% and 34.7–46.5%, respectively, with the change in the proportion used during co-processing. Additionally, with the increase in SO2 concentration, the total concentration and TEQ value of dioxins decreased by 11.1–29.8% and 5.1–26.9%, respectively. Furthermore, the low-chlorinated dioxin congeners increased and high-chlorinated ones decreased. Most importantly, it was revealed that the dioxin formed during co-processing was suppressed by the deactivation of metal catalysts and the reduction of chlorine sources. These findings will facilitate the rational control of dioxin emissions with the co-processing of WPCB in an Ausmelt furnace.